2017
DOI: 10.1177/0025802417747166
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of contaminating amplified short tandem repeat products by autoclaving and ultraviolet irradiation

Abstract: DNA contamination can result in false interpretation of short tandem repeat (STR) DNA typing. Proper decontamination is particularly required in forensic DNA laboratories where probative value of the evidence may be affected. The aim of this study was to establish an effective DNA decontamination procedure for amplified STR products focusing on laboratory-related contamination. We verified the effectiveness of thermally and temporally extended autoclaving and ultraviolet irradiation for the elimination of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Further, we collected and processed more blanks, including reagents, kit and sequencing reaction controls as well as positive controls on each reaction plate to enable us identify contaminants in reagents and kits [30]. We also included controls in the sequencing reactions and took additional steps to reduce supplies and work area contamination, including wiping down the hood and work bench with bleach as well as 70% ethanol and exposing the hood and supplies to ultra-violet light for at least 1 hour before starting work [32][33][34]. In this expanded study, real time qPCR analysis showed the VR samples had similar bacterial biomass as in the pilot study while blanks, placental, maternal and cord blood samples had decreased bacterial 16S rRNA gene DNA levels, frequently below the limit of accurate detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we collected and processed more blanks, including reagents, kit and sequencing reaction controls as well as positive controls on each reaction plate to enable us identify contaminants in reagents and kits [30]. We also included controls in the sequencing reactions and took additional steps to reduce supplies and work area contamination, including wiping down the hood and work bench with bleach as well as 70% ethanol and exposing the hood and supplies to ultra-violet light for at least 1 hour before starting work [32][33][34]. In this expanded study, real time qPCR analysis showed the VR samples had similar bacterial biomass as in the pilot study while blanks, placental, maternal and cord blood samples had decreased bacterial 16S rRNA gene DNA levels, frequently below the limit of accurate detection.…”
Section: Discussionmentioning
confidence: 99%
“…Placental samples did not segregate by study group and did not segregate from blank controls. PCoA analysis based on Jaccard distances is shown wearing masks to cover operators' skin and respiratory tract respectively), attention to work environment (wiping down bench and hood with bleach, use of laminar flow hood) [29,[32][33][34]36], sample processing (microbial DNA extraction and PCR amplification) [36] and inclusion of negative (blank) and positive controls [12,21,30,32]. Beyond sample collection and sample processing, several bioinformatic techniques have been developed to detect and subtract contaminants in studies of low bacterial biomass tissues but these all have their limitations and little is known so far of the relative effectiveness of the different techniques [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%